2010
DOI: 10.1007/s13173-010-0011-5
|View full text |Cite
|
Sign up to set email alerts
|

EvolTrack: improving design evolution awareness in software development

Abstract: Software differs from most manufactured products because it is intangible. This characteristic makes it difficult to detect, control, and understand how it evolves. This paper presents an approach based on software visualization that can detect and externalize design evolution made in a software project during its initial development or at any further phase. By using this approach, a developer can be aware of the current state of the software as a whole and can additionally verify if the current design, also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…• Palantír: Supports the perception of artifacts for developers using Configuration Management Systems (CMS) (Sarma et al, 2003) • Ariadne: Presents the socio-technical relationship among the artifacts. It increases the perception of developers about the social dependencies of their work (de Souza et al, 2004) • Augur: Provides information on artifacts structure and their related activities in distributed software development (Froehlich and Dourish, 2004) • ADAMS -ADvanced Artefact Management System: Supports traceability and change management of artifacts during software development (de Lucia et al, 2005) • ProjectWatcher: supports the perception of the activities in distributed software development projects (Gutwin et al, 2005) • EvolTrack: supports the perception of software evolution throughout development cycle (Cepêda et al, 2010) The main aspects identified in these tools were:…”
Section: Context Awareness On Software Artifactsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Palantír: Supports the perception of artifacts for developers using Configuration Management Systems (CMS) (Sarma et al, 2003) • Ariadne: Presents the socio-technical relationship among the artifacts. It increases the perception of developers about the social dependencies of their work (de Souza et al, 2004) • Augur: Provides information on artifacts structure and their related activities in distributed software development (Froehlich and Dourish, 2004) • ADAMS -ADvanced Artefact Management System: Supports traceability and change management of artifacts during software development (de Lucia et al, 2005) • ProjectWatcher: supports the perception of the activities in distributed software development projects (Gutwin et al, 2005) • EvolTrack: supports the perception of software evolution throughout development cycle (Cepêda et al, 2010) The main aspects identified in these tools were:…”
Section: Context Awareness On Software Artifactsmentioning
confidence: 99%
“…The DiSEN-CollaborAR approach combines some positive aspects of other approaches and tools Sarma et al (2003), de Souza et al 2004 2011and Cepêda et al (2010) to support the context awareness about software artifacts, such as capturing contextual information from Version Control System and UML CASE Tool and the presentation by graphs. However, DiSEN-CollaborAR approach explores also other challenges such as the combination of traceability links between different types of software artifacts -source code and class diagram.…”
Section: Overview Of the Disen-collaborar Approachmentioning
confidence: 99%
“…EvolTrack [13] is an approach that supports the awareness on the evolution of software during the development cycle. The tool extracts structural information about software artifacts, such as classes and packages from version control systems and workspaces for development.…”
Section: Related Workmentioning
confidence: 99%